Numerical analysis of Au/Blood aggregate nanofluid flow enclosed under the influence of magnetic field and thermal radiation - L.O. Aselebe; O.A. Ajala; A.O. Akindele; B.B. Lamidi; A.D. Ohaegbue; P. Adegbite; S.O. Salawu (Results in Materials)
In the cause of enhancing the heat and mass transfer of blood, nanoparticles are being introduced to give an improved heat exchanger in human systems. Nanofluid is a viable heat-carrier fluid, which serves as a cooling agent in drug delivery systems and improves their performances. However, the stability of nanoparticles in the base fluid is one of its challenges that needs more attention. This work investigates the aggregate of gold nanoparticles and blood-based fluid in the presence of both thermal radiation and magnetic fields. To have a better understanding and prediction of this physical phenomenon, a mathematical model of the system of governing Partial Differential Equations (PDEs) were formulated and transformed into a system of coupled third-order non-linear boundary values differential equations by similarity techniques. The boundary value in Ordinary Differential equations (ODEs) were reduced into the system of first-order initial value ODEs using the shooting approach alongside the Runge-Kutta Fehlberg fourth-fifth order (rkf45) method with the help of Python 3.0 software. The numerical results of the influence of aggregate nanoparticles on the velocity and temperature profiles were displayed graphically and the effect of thermo-physical parameters on skin friction coefficient and Nusselt number were shown in tables. It was found that as thermal radiation upsurges the temperature profile escalates for both with and without aggregate nanoparticles. Likewise, rises in magnetic fields raise the temperature profile of the gold-blood nanofluid. Nevertheless, the velocity profile declines as the magnetic field intensifies. This present work can be of great help in the medical field where drug delivery is paramount. Also the result has a significant impact on the possibility of utilizing the interaction between aggregate gold nanoparticles in blood-based fluid, which improved the system's mass and heat transfer.